2018
DOI: 10.1186/s40659-018-0155-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of phosphorus stress responsiveness in the seedlings of Dongxiang wild rice (Oryza rufipogon Griff.)

Abstract: BackgroundLow phosphorus availability is a major factor restricting rice growth. Dongxiang wild rice (Oryza rufipogon Griff.) has many useful genes lacking in cultivated rice, including stress resistance to phosphorus deficiency, cold, salt and drought, which is considered to be a precious germplasm resource for rice breeding. However, the molecular mechanism of regulation of phosphorus deficiency tolerance is not clear.ResultsIn this study, cDNA libraries were constructed from the leaf and root tissues of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…The surface sterilized seeds were rst soaked in petri dishes containing 20 mL deionized water at room temperature for 3 days. Then the seeds were selected with same growth and planted in the plastic pot in a climate control chamber at day/night 14 h/10 h (30℃/26℃) [18]. Germinated seeds with coleoptiles 10 mm approximately in length, adding Yoshida culture medium (pH5.8) [46].…”
Section: Plant Materials and Phosphorus De Ciency Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface sterilized seeds were rst soaked in petri dishes containing 20 mL deionized water at room temperature for 3 days. Then the seeds were selected with same growth and planted in the plastic pot in a climate control chamber at day/night 14 h/10 h (30℃/26℃) [18]. Germinated seeds with coleoptiles 10 mm approximately in length, adding Yoshida culture medium (pH5.8) [46].…”
Section: Plant Materials and Phosphorus De Ciency Treatmentmentioning
confidence: 99%
“…found in the northernmost distribution latitude to date, which is a unique wild plant resource in Jiangxi Province. Because DXWR grows in the wild for a long time and suffers from various adverse environmental choices, it has more abundant genetic diversity than cultivated rice, and contains a large number of excellent genes that are not or have been lost in cultivated rice, including low-P resistance [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus (P) is an essential trace element required for proper plant growth and development where it plays an important role in energy transfer, signal transduction, photosynthesis, and respiration [77]. A comparative transcriptome study has been carried out in leaf and root tissues during phosphorus stress to elucidate their molecular mechanisms [78]. The transcriptome analysis suggested that many differentially expressed TFs and functional genes were uniquely involved in multiple regulatory pathways (including RNA transport and mRNA monitoring path) during phosphorus deficiency tolerance [78].…”
Section: Transcriptome Data For Trace Element Stressmentioning
confidence: 99%
“…A comparative transcriptome study has been carried out in leaf and root tissues during phosphorus stress to elucidate their molecular mechanisms [78]. The transcriptome analysis suggested that many differentially expressed TFs and functional genes were uniquely involved in multiple regulatory pathways (including RNA transport and mRNA monitoring path) during phosphorus deficiency tolerance [78].…”
Section: Transcriptome Data For Trace Element Stressmentioning
confidence: 99%